Analisis Desain Cetakan Paving Blok Hexagonal - Saputro, Bagas Adi; Yunus, Muhammad; Andi, Zulfan Yus (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Plastic molds offer lighter weight, ease of design modification, and the ability to produce very large quantities of products due to the ability to cast with multiple molds simultaneously. However, they are susceptible to thermal deformation due to pressure during the casting process. This condition can cause dimensional deviations outside the tolerance limits set by the British Standards Institution (BSI), which is ± 2 mm. This research focuses on the design analysis of hexagonal paving block molds made of Polypropylene (PP) using the SolidWorks Simulation approach to evaluate the effect of variations in the number of reinforcements (ribs) on the deformation and stiffness of the mold design. Paving block models have four design configurations: no ribs, one rib, two ribs, and three ribs. The analysis results show that all designs are still within the maximum deformation tolerance limit, but increasing the number of ribs significantly increases stiffness and decreases total deformation. The three-rib configuration produces a minimum deformation of 0.5059 mm, making it the most optimal design in maintaining mold dimensional stability. This research provides a scientific basis for the development of optimal, precise, and BSI-standardized paving block molds with Polypropylene material for mass production of paving blocks.